(untitled) (Theatrum historiae, 2017)
The following article primarily analyses the operation of the Lutheran Legation Chapel during the long-term residency of the Danish Envoy, Andreas Pauli von Liliencron, in Vienna. The targeted support for the denominational minorities in Vienna and Copenhagen by the legation envoys caused numerous conflicts on both sides. The ways of resolving these disputes eventually become reminders of the extraordinary dynamism of international relations during the second half of the 17th Century.